(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study examines the role of the Financial Services Authority (OJK) in maintaining the stability of legal economics in Indonesia through various regulatory policies and financial education. Using a qualitative approach, this research involves in-depth interviews with several SMEs, students, and lecturers to explore the impact of the policies implemented by OJK. The findings of this study indicate that the regulations issued by OJK have provided clear legal certainty for SMEs, while also improving financial literacy among the public. Furthermore, interviews with lecturers highlight the urgency of strengthening OJK regulations, especially in the face of the rapidly growing digitalization phenomenon in the financial sector. This research underscores the importance of OJK's policies in maintaining Indonesia's economic stability and suggests that these policies must continue to evolve and adapt to the increasingly complex global dynamics. The role of OJK is crucial in anticipating the various challenges that Indonesia's economy will face in the future.